(untitled) (Research, Society and Development, 2021)
The textile industry has developed and grown more and more, with this it has been using more dyes, so a large volume of highly colored and contaminated effluents is generated, these effluents, if discarded without prior treatment in water bodies, can generate environmental problems bass. A simple, efficient and cheap way to carry out the removal of these dyes is using the adsorption technique. With that, the present work intends to demonstrate if passion fruit residues, the seeds, which have low added value, can be used as alternative adsorbents for the treatment of textile effluents. Therefore, the objective of this work was to evaluate the passion fruit seeds as an alternative adsorbent for the Nylosan blue N-BLN textile dye, in addition to evaluating the effect of the ionic strength and pH of the solution on the adsorption efficiency and to evaluate the viability of the desorption process. The adsorption studies were carried out in a fixed bed column using in natura passion fruit residues and subjected to chemical treatments with HCl. The acid treatment increased the biomass adsorption efficiency. The ionic strength had little influence on the adsorption process. The pH influenced the adsorption process, and the best pH value was equal to two. The desorption process was possible to happen, using sodium hydroxide NaOH as an extracting solution. The adsorptive capacity for seeds was 10.2 and 20.2 mg g-1 for biomass in natura and treated with HCl.